Connecting Metabolic Rewiring With Phenotype Switching in Melanoma - Falletta, Paola; Goding, Colin R.; Vivas-García, Yurena (Frontiers in Cell and Developmental Biology, 2022)
Melanoma is a complex and aggressive cancer type that contains different cell subpopulations displaying distinct phenotypes within the same tumor. Metabolic reprogramming, a hallmark of cell transformation, is essential for melanoma cells to adopt different phenotypic states necessary for adaptation to changes arising from a dynamic milieu and oncogenic mutations. Increasing evidence demonstrates how melanoma cells can exhibit distinct metabolic profiles depending on their specific phenotype, allowing adaptation to hostile microenvironmental conditions, such as hypoxia or nutrient depletion. For instance, increased glucose consumption and lipid anabolism are associated with proliferation, while a dependency on exogenous fatty acids and an oxidative state are linked to invasion and metastatic dissemination. How these different metabolic dependencies are integrated with specific cell phenotypes is poorly understood and little is known about metabolic changes underpinning melanoma metastasis. Recent evidence suggests that metabolic rewiring engaging transitions to invasion and metastatic progression may be dependent on several factors, such as specific oncogenic programs or lineage-restricted mechanisms controlling cell metabolism, intra-tumor microenvironmental cues and anatomical location of metastasis. In this review we highlight how the main molecular events supporting melanoma metabolic rewiring and phenotype-switching are parallel and interconnected events that dictate tumor progression and metastatic dissemination through interplay with the tumor microenvironment.